Comarca do Rio das Mortes em Minas Gerais: expansão urbana nos séculos XVIII e XIX - Marilia de Fatima Dutra de Avila Carvalho (2015)
Starting from discussion of urban expansion, were investigated seven waves of urban expansion within the limits of the Comarca do Rio das Mortes in Minas Gerais between 1714 and 1891. Our spatial area is the urban network of the region, which expanded from two initial urban centers, which were São João Del-Rei and São José Del-Rei (current Tiradentes) to 317 urban centers, today. The Comarca do Rio das Mortes lasted a long-term (177 years) in an extensive territory (120 thousand km²). The urban network of the region resulted from the merger of three networks: the ecclesial network, the civil network and the judicial network, analyzed separetely. State and Church acted in an imbricated way during the Eighteenth and Nineteenth centuries in Minas Gerais during the Padroado regime. We identify the rules of the urban sprawl phenomenon in the region: there was religion in the public sphere; State and Church collaborated in the urban foundation; urban expansion of the Comarca do Rio das Mortes accompanied economic development. As objectives, we presented the methodological basis for a regionalized macro-analysis of the District; we constructed a periodization of urban expansion in the region through a detailed analysis of the ecclesial, civil and judicial networks. We classified the urban expansion waves in the region, in the Eighteenth and Nineteenth centuries. The product achieved by the thesis is the classification periodized of the waves of urban network expansion in the region, in order to contribute to advancing the legacy of progressive researches on urban spatial differentiation of the territory of Minas Gerais in the Eighteenth and Nineteenth centuries. It was concluded that the urban network of the region grew by seven waves of urban sprawl. The three networks ecclesiastical, civil and judicial grew intertwined. State and Church collaborated in urban settlements, and the ecclesial network was the largest contributor in the urban expansion of the Comarca.